China past forward - forever Beijing - Chang, Liu; Randle, Jim; Wolf, Erika; Gibbons, James (Discovery Channel, 2003)
Not too far from the Forbidden City, Beijing's secret treasures are slowly vanishing. This program captures the dilemmas, contemporary and otherwise, faced by a people undergoing rapid change in their new century.